Tit for tat? A study on the relationship between work connectivity behavior after-hours and employees’ time banditry behavior - Li, Jingya; Chen, Hao; Wang, Liang; Bao, Jiaying (Frontiers in Psychology, 2024)
Based on Conservation of Resources Theory, this study tries to reveal the mechanism of action of work connectivity behavior after-hours triggering employees’ time banditry behavior. By using Mplus7.4 software the analysis of 429 leader-employee paired data collected in three stages reveals that work connectivity behavior after-hours has a positive effect on work alienation and psychological distress. Work alienation and psychological distress mediates the relationship between work connectivity behavior after-hours and employees’ time banditry behavior, respectively. In addition, organization-based self-esteem mitigates the positive effects of work connectivity behavior after-hours on work alienation and psychological distress, which in turn also moderates the indirect effects of work connectivity behavior after-hours on employees’ time banditry behavior through work alienation and psychological distress, respectively. This study provides practical guidance for organizations to reduce employee time banditry behavior and human resource management practices in the new technological environment.